(3ahGFO GdbGVi CHh WGgQ eMeO Hf CMeO Hf YHO Gddg Hf fUQ Hf HLjQ GdPgdi aj GdMOjKs - (3GdOQGbWfj , CHh GdMSf,J (B385 (3g` s
(3ChdgG (B:s
(3bQCJ Ydi GdTjN GdCLd CHj GdZfGFe GdeSde Hf CMeO Hf Ydi GdfUjHi GdeGRei Efi cfJ ai GdLGgdjI CQi GdfGS Ydi VdGdI hdG CQi GdChKGf s
(3BNQgG (B:s
(3Yf CHGf Hf YKeGf Yf CHjg Cf GdfHi Udi Gddg Ydjg hSde (B: ( (3bGd NjGQce ef JYde GdbQCf hYdeg (B) (3GfJgi GdLRA GdNGeS hGdYTQhf HMeO Gddg hefg s
(3GdfSNI HgG MhGTs
(3Ydjg SeGYGJ cKjQI ef GdYdeGA ai GdbQf GdSGHY hGdKGefs
(3JHUQI GdYfhGf (B:s
(3EfJbGA s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B157s
Keywords: (3GdMOjK h GdeUWdMs